Characterisation of Fault-Related Mn-Fe Striae on the Timpa Della Manca Fault (Mercure Basin, Southern Apennines, Italy) - Sabrina Nazzareni; Luciana Mantovani; Mattia Pizzati; Danilo Bersani; Tiziano Boschetti; Ambra Palmucci; Daniele Cirillo; Francesco Brozzetti (Geosciences)
The Quaternary Mercure basin is a complex fault structure located in the Pollino region of the southern Apennines (Italy). A persistent seismic gap makes the Mercure basin structure one of Italy’s highest seismic risk zones. The southernmost termination of the Mercure basin is the Timpa della Manca fault. The fault’s mirror is characterised by distinctive, lineated, black-coloured striae decorating a cataclasite made of carbonate clasts. These black-coloured striae consist of a mixture of Mn phases, including hollandite, todorokite, birnessite, and orientite, which are associated with goethite and hematite along with minor amounts of phyllosilicates (chlorite, muscovite), quartz, and sursassite. This mineral association and their phase stability suggest that hydrothermal circulating fluids may have mobilised and re-precipitated low-temperature Mn hydrous phases within the shear zone, leaving remnants of higher-temperature minerals. Oceanic crust remnant blocks within the Frido Unit appear to be the most likely source of the Mn. The uniqueness of the Mn striae on the Timpa della Manca fault offers intriguing insights into fluid circulation within the Mercure basin tectonic system, with potential implications for the seismotectonic characteristics of the Pollino region.